(untitled) (Baghdad Science Journal, 2019)
The fresh water green alga Chlorella vulgaris was selected to study its ability to degrade one of polycyclic aromatic hydrocarbon (PAHs)known is anthracene (ANT). ANT is widely used in artificial products such as wood preservatives; insecticides; dye and coating materials. This algae was cultivated in CH-10 medium under constant laboratory conditions and exposed to different concentrations (1, 3, and 5 mg/l) of anthracene for 3, 5, 7, 9 and 15 days, with the concentration of ANT measured by high performance liquid chromatographic analysis (HPLC). The results showed that C.vulgaris has high ability to reduce anthracene to 80% at 1mg/Lcon centration after 3 days and 100% after 5 days, while at 3 and 5 mg / L concentration, the highest percentages were 89% and 99%, respectively after 9 days, with the complete removal (100%) was achieved after 15 days. The results indicate that this alga(C. vulgaris) has high ability for remediation of ANT and yield not toxic compound to environment